Utilization of egg shell-HCI reaction in illustrating the factors that effect reaction rates - Dumancas, Chester C. ([Quezon City s.n.], 1974)
The reaction of egg shell pieces with dilute hydrochloric acid was used to show the effects of concentration, total surface area of the solid reactant and temperature on the rate of the reaction. The researcher found out that the reaction was: (1) second order with respect to the acid concentration (2) chemically controlled rather than diffusion controlled (3) proportional to the total surface area and (4) requiring an activation energy of about 3,700 calories per mole.
Thesis (Master of Arts in Teaching Chemistry)--University of the Philippines.
Keywords: Chemical reaction, Rate of